Advanced characterization of the structuration of ionic liquids in a copolyester. (September 2019) - Megevand, Benjamin; Pruvost, Sébastien; Duchet-Rumeau, Jannick
Graphical abstract: Highlights: Addition of phosphonium Ionic Liquid interestingly modifies mechanical properties of PBAT. Depending on the counter anion, the ionic liquid is miscible or not with PBAT. AFM nanomechanical mappings highlights the complex structurating mechanism. Dielectric spectroscopy helps to identify rigid and mobile amorphous phases. Abstract: The influence of the addition in small amounts (2 wt%) of two phosphonium–based ionic liquids (ILs) on the nanostructuration and mechanical properties of a poly(butylene-adipate- co -terephtalate) (PBAT) matrix was investigated using complementary approaches. Dielectric spectroscopy and nanomechanical characterizations using atomic force microscopy (PeakForce QNM mode, Bruker) were used along X-ray diffraction, differential scanning calorimetry and dynamic mechanical analysis to explain the mechanical (tensile) properties of each system. The semicrystalline matrix was found to have a spherulitic structure, with crystalline lamellae composed of butylene terephtalate units. In one case, the addition of an immiscible phosphonium-phosphinate ionic liquid (il-TMP) to the matrix, inducing a 33% increase of the strain at break, was found via AFM to induce a nodular microstructure with dissipative effects and smooth nodule-matrix interphases. In the other case, a phosphonium-chloride ionic liquid (il-Cl), being miscible in the amorphous phases, increases the chain mobility of the mobile amorphous fraction (MAF) consisting of free polymer chains, while it hinders the relaxation, thus chain movements, of the confined rigid amorphous fraction (RAF). This double effect induced a moderate macroscopic Young's modulus drop (less than −20%) with a +60% increase of the strain at break, and no significant influence on thermal properties. AFM in situ mechanical measurements, along with dielectric spectroscopy, allowed to propose complete mechanisms for the ILs-matrix interactions, highlighting the potential of such additives for the tuning of the properties of polymers.